2022
DOI: 10.1002/lary.30050
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Incision Approach for Hypoglossal Nerve Stimulator Placement: A Single Institution Assessment

Abstract: Objective(s): Upper airway stimulator (UAS) placement is a treatment for obstructive sleep apnea (OSA) with few complications and low morbidity. UAS placement has traditionally been performed using a three-incision approach, however, it has been implanted using a two-incision approach. This approach could significantly decrease operation time without a difference in postoperative complications, demonstrating its safety and feasibility for UAS placement. The objective was to assess operative time and complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…This finding supports the notion that, with careful dissection and placement, the 2‐incision technique is able to successfully place the sensing electrode within the intercostal space without respiratory signal interference from cardiac artifact. This, along with the other previously described benefits of the 2‐incision approach, 16 , 21 , 22 supports the transition to this technique by sleep surgeons.…”
Section: Discussionsupporting
confidence: 80%
“…This finding supports the notion that, with careful dissection and placement, the 2‐incision technique is able to successfully place the sensing electrode within the intercostal space without respiratory signal interference from cardiac artifact. This, along with the other previously described benefits of the 2‐incision approach, 16 , 21 , 22 supports the transition to this technique by sleep surgeons.…”
Section: Discussionsupporting
confidence: 80%
“…There have been reports of pneumothoraces occurring during both techniques 15,23,24 . In our study, <10 of 486 HNS implantations performed after FDA approval were complicated by a pneumothorax.…”
Section: Discussionmentioning
confidence: 59%
“…23 Kent et al and Sagalow et al found no significant differences in rates of adverse events comparing the 2-and 3-incision approaches. 23,24 There have been reports of pneumothoraces occurring during both techniques. 15,23,24 In our study, \10 of 486 HNS implantations performed after FDA approval were complicated by a pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective review comparing the 2 techniques showed similar complication rates but a statistically significant decrease in average operation time from 143 to 129 minutes ( P < .001). 46 Upcoming improvements are focused on having the inspiration sensor incorporated within the implantable pulse generator, further decreasing procedure time and risk of complication for the device.…”
Section: Discussionmentioning
confidence: 99%